Combining ability, heterosis and heritability of agronomic traits and resistance to maize streak virus in maize inbred lines - Ige, Adenike Damilola (2017)
A thesis submitted to The Department of Crop and Soil Sciences, Kwame Nkrumah University of Science and Technology, Kumasi, Ghana in partial fulfillment of the requirements for the degree of Master of Philosophy in Plant Breeding.